The Role of Culture and Community: in Developing Effective Organization - Hadi, Achmad Setyo (Universitas Prasetiya Mulya, 2008)
This paper analyzes the relations between culture and communities. The interesting cultural aspects of organizations are, as we have seen, not what is unique for a single organization, but deeper and broader patterns that to some extent are part of a more general business, industrial, or community culture. Understanding of cultural manifestations in organizations, even those that are dominant and broadly shared on the local level, is that it makes us realize the management’s influence is, after all, restricted. National culture, class culture, and the cultures of professional and occupational communities put strong imprints on organization. An important additional factor, not often addressed in either research or theorizing, that may help explain the variation in the communal nature of organizations over time and across locales are the social values and norms that get embedded in particular theories and perspectives about people and organizations, perspectives that do not simply take place but that are promulgated by interest groups with particular agendas and beliefs.